The Incidence and the Clinical Significance of the Gray Zone in the Clinical Phases of Chronic Hepatitis B Virus Infection - Asreah , Rabah H.; Alkagany, Jawad A. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: five clinical phases were described in patients with chronic (HBV) infection: HBeAg- positive HBV infection, HBeAg- positive chronic HB, HBeAg negative HBV infection, HBeAg-negative CHB and occult HBV infection.Aim: This study aimed to determine the incidence of the unclassified phase (gray zone) in chronic hepatitis B patients and its significant in the clinical practice. Patients and methods: The study was conducted retrospectively on 109 patients' who have HBsAg positive for more than 6 months. The data recorded include; HbeAg and anti-HBe Ab, ultrasound of the abdomen, HBV DNA load and alanine aminotransferase (ALT), accordingly; we classify the patients to known clinical phases. Patients who were unfit one of these phases considered to be in the gray zone and subsequently sent for liver fibroscan to determine the fibrosis stage. Results: The mean age of our patients was 34.25 (±13.93) years with 54.12% being males. The mean viral load was 5,885,490 IU/ml and mean ALT was 56.22 (±89.88) U/L. eight  patients (7.3%) were in the HBeAg+ve HBV infection, 13 patients (11.9%) were in HBeAg+ve CHB . Thirty four patients (31.1%) were in the HBeAg-ve HBV infection and 23 (21.1%) were in HBeAg-ve CHB phase, both were showed a higher occurrence with age> 35 years. Thirty one (28.4%) further patients failed to identify with any of the four phases (normal ALT with HBV load > 2000 IU/ml), this group also showed significant relation to age above 35 years and 12 patients (38.8%) had significant fibrosis on fibroscan.Conclusions: A considerable number of patients with chronic HBV infection have persistently normal ALT levels, despite elevated levels of viral load; this is known as the "grey zone" phase. These patients merit close follow up with short-interval measurement of liver enzymes, liver fibroscan and biopsy may be considered.